REGULATORY EFFECTS OF RUMEX OBTUSIFOLIUS AND HYPERICUM ALPESTRE EXTRACTS ON THE QUANTITY OF IL-2 IN IN VITRO AND IN VIVO CANCER MODELS (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
The increase in the incidence of cancer in Armenia and around the world is a serious problem, and the chemical interventions used in cancer therapy, which partially have a therapeutic effect, are often accompanied by the destruction of normal body cells. Therefore, it is necessary to search for new alternative treatments that will be highly effective and accompanied by a small number of side effects. From this point of view, several medicinal plants used in traditional medicine can be considered new, effective means of treating cancer, since they have an immunostimulating effect on individual parts of the human immune system. Considering all this, the work aimed to study the quantitative changes in the production of interleukin-2 in the blood and tumor of rats under the influence of plant extracts in an experimental model of DMBA (7,12-dimethylbenz[a]anthracene)-induced breast cancer, as well as cell cultures of breast cancer and lungs. We showed that Hypericum alpestre and Rumex obtusifolius extracts have a pronounced anticancer effect by increasing interleukin-2 (IL-2) levels in the blood and tumors of rats. They also brought quantitative changes in phosphoinositol-3-kinase (PI3K), which plays a key role in cancer development. This could be the basis for developing new anticancer or cancer-preventing drugs derived from more potent H. alpestre and R. obtusifolius herbs.
Keywords: breast cancer; herb; IL-2; PI3K/AKT pathway; Rumex obtusifolius; Hypericum alpestre; immunotherapy